Degeneration of the Cerebellum in Huntington's Disease (HD): Possible Relevance for the Clinical Picture and Potential Gateway to Pathological Mechanisms of the Disease Process. (21st September 2012) - Rüb, Udo; Hoche, Franziska; Brunt, Ewout R.; Heinsen, Helmut; Seidel, Kay; Del Turco, Domenico; Paulson, Henry L.; Bohl, Jürgen; von, Charlotte; Vonsattel, Jean‐Paul; Korf, Horst‐Werner; den, Wilfred F.
Abstract Huntington's disease (HD) is a polyglutamine disease and characterized neuropathologically by degeneration of the striatum and select layers of the neo‐ and allocortex. In the present study, we performed a systematic investigation of the cerebellum in eight clinically diagnosed and genetically confirmed HD patients. The cerebellum of all HD patients showed a considerable atrophy, as well as a consistent loss of Purkinje cells and nerve cells of the fastigial, globose, emboliform and dentate nuclei. This pathology was obvious already in HD brains assigned Vonsattel grade 2 striatal atrophy and did not correlate with the extent and distribution of striatal atrophy. Therefore, our findings suggest (i) that the cerebellum degenerates early during HD and independently from the striatal atrophy and (ii) that the onset of the pathological process of HD is multifocal. Degeneration of the cerebellum might contribute significantly to poorly understood symptoms occurring in HD such as impaired rapid alternating movements and fine motor skills, dysarthria, ataxia and postural instability, gait and stance imbalance, broad‐based gait and stance, while the morphological alterations (ie ballooned neurons, torpedo‐like axonal inclusions) observed in the majority of surviving nerve cells may represent a gateway to the unknown mechanisms of the pathological process of HD.